2019
DOI: 10.1029/2018gl081325
|View full text |Cite
|
Sign up to set email alerts
|

History‐Dependent Threshold for Motion Revealed by Continuous Bedload Transport Measurements in a Steep Mountain Stream

Abstract: To explore the causes of history‐dependent sediment transport in rivers, we use a 19‐year record of coarse sediment transport from a steep channel in Switzerland. We observe a strong dependence of the threshold for sediment motion (τc) on the magnitude of previous flows for prior shear stresses ranging from 104 to 340 Pa, resulting in seasonally increasing τc for 10 of 19 years. This stabilization occurs with and without measureable bedload transport, suggesting that small‐scale riverbed rearrangement increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
89
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 56 publications
2
89
0
Order By: Relevance
“…This theory suggests that low, inter-flood flow periods will have no effect on bed stability and bed restructuring will only occur during flood events which result in active bedload transport modifying surface stability. However, field Reid et al, 1985;Masteller et al, 2019) and flume (Paphitis and Collins, 2005;Monteith and Pender, 2005;Haynes and Pender, 2007;Ockelford and Haynes, 2013;Masteller and Finnegan, 2017) data suggests that both uniform and graded beds appear to progressively stabilize even when subjected to the low shear stresses experienced during inter-flood flow periods.…”
Section: Introductionmentioning
confidence: 99%
“…This theory suggests that low, inter-flood flow periods will have no effect on bed stability and bed restructuring will only occur during flood events which result in active bedload transport modifying surface stability. However, field Reid et al, 1985;Masteller et al, 2019) and flume (Paphitis and Collins, 2005;Monteith and Pender, 2005;Haynes and Pender, 2007;Ockelford and Haynes, 2013;Masteller and Finnegan, 2017) data suggests that both uniform and graded beds appear to progressively stabilize even when subjected to the low shear stresses experienced during inter-flood flow periods.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling flow and bed load transport in mountain stream is complex because patches of mobile sediments coexist with immobile structures such as steps or isolated boulders (Green et al, 2015; Laronne et al, 2001; Yager et al, 2012). Furthermore, critical dimensionless shear stress in mountain streams (i.e., Shields stress) is very difficult to model, due to its high variability in time (Masteller et al, 2019) and space (Monsalve et al, 2016), modulated by changes in local channel slope (Lamb et al, 2008) and relative submergence of sediments (Lenzi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To further study such "memory" effect of antecedent flow on the sediment transport during a subsequent flood, a number of flume experiments as well as field surveys have been conducted in the past decade, and different terms have been proposed, including "stress history effect" (Monteith and Pender, 2005;Paphitis and Collins, 2005;Haynes and Pender, 2007;Ockelford and Haynes, 2013), "flood history effect" (Mao, 2018), "flow history" (Masteller et al, 2019), etc. Given that all these terms are similar, here we adopt the term "stress history" in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the previous research about stress history is either under conditions with relatively low sediment transport or with relatively short durations of sediment transport in order to capture the threshold of sediment motion (Monteith and Pender, 2005;Paphitis and Collins, 2005;Haynes and Pender, 2007;Ockelford and Haynes, 2013;Masteller and Finnegan, 2017;Ockelford et al, 2019). On the other hand, other researchers have found that exceptionally high discharge events can reduce critical shear stress by disrupting particle interlocking and breaking of bed structure (Turowski et al, 2011;Yager et al, 2012;Ferrer-Boix and Hassan 2015;Masteller et al, 2019). Flume experiments by Masteller and Finnegan (2017) also indicate an increase in the number of highly mobile, highly protruding grains in response to sediment transporting flows.…”
Section: Introductionmentioning
confidence: 99%